Reflections on my role as a mental health service user co-applicant in a randomized control trial. (1st February 2020) - Lea, Laura; Byford, Sarah; Coney, Yve; Crane, Rebecca; Fagabemi, Natalia; Gurney, Tony; Leigh-Phippard, Helen; Rosten, Claire; Simms, Kate; Strauss, Clara
Abstract : This is not a research paper but a personal and collective reflection of patient and public involvement (PPI) for the LIGHTMind 2 randomized control trial (www. isrctn. com/ISRCTN13495752). This trial compares two guided self-help psychological interventions for depression, and is delivered in the UK NHS Improving Access to Psychological Therapy services. The paper is the result of my reviewing our PPI 18 months into the trial. The PPI includes myself as a research team member and co-applicant, with lived experience of depression, mindfulness and cognitive behaviour therapy. There is a Lived Experience Advisory Panel of six people with lived experience of depression or mindfulness, who advise the researchers. Two people with lived experience of mental health difficulties and knowledge of PPI attend the Trial Steering Committee. This paper includes comments from some of the other people with lived experience and from researchers involved in the trial, included as co-authors. I offer the Johari window (Luft, 1970) and the 4Pi National Involvement Standards (NSUN, 2018) as a way of positioning the value of PPI. Developing relationships within PPI is identified as a way of moderating the fear that some people experience as they work with researchers. I describe the importance of principles that incorporate explicit statements about the value of PPI.